PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA PADA PROYEK KONSTRUKSI JALAN TERHADAP KINERJA KARYAWAN PT FAHMITRA RAHAYU - Rati Utami Sari (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
ABSTRACT The purpose of this study was to research and get an overview of the Implementation of the Occupational Safety and Health Management System in Road Construction Projects on Employee Performance at PT Fahmitra Rahayu. The approach method used in this study is to look for associative relationships that are causal, namely with a quantitative descriptive approach.. In this study there are independent variables (variables that affect) and dependent (influenced). Analysis of the independent variable (X) which consists of work safety and occupational health variables on the dependent variable, namely employee performance (Y). Therefore, in this study the Statistical program Product and Service Solutions (SPSS) 23, by applying this technique, the hypothesis can be tested which states that there is a partial effect and a simultaneous effect between the independent variable (X), namely work safety (X1) and occupational health (X2) on the dependent variable (Y ), namely employee performance. The Occupational Safety Program has a positive and significant effect on the performance of employees of PT. Fahmitra Rahayu, at the regression output the significance value shows the work safety variable on performance is 0.002 <0.05. t count 2.017> 2.014 t table means that it can be concluded that if work safety has a significant positive effect on employee performance, it can be concluded that the hypothesis is accepted meaning that there is a significant effect of work safety (X1) on employee performance (Y). Occupational health has a positive and significant effect on the performance of employees of PT. Fahmitra Rahayu. The results of this test support this research hypothesis or H2 has a positive effect on employee performance. positive and significant influence on employee performance. Employee performance is positively and significantly influenced by the variables of occupational safety and health, which means that it indicates that the variables of occupational safety and health have a positive effect on the performance of employees of PT. Famitra Rahayu, so that the better the application of occupational safety and health, the employee's performance will increase.